The development of the larval nervous system, musculature and ciliary bands of Pomatoceros lamarckii (Annelida): heterochrony in polychaetes. - McDougall, C; Chen, W; Shimeld, S; Ferrier, D (2006)
BACKGROUND: To understand the evolution of animals it is essential to have taxon sampling across a representative spread of the animal kingdom. With the recent rearrangement of most of the Bilateria into three major clades (Ecdysozoa, Lophotrochozoa and Deuterostomia) it has become clear that the Lophotrochozoa are relatively poorly represented in our knowledge of animal development, compared to the Ecdysozoa and Deuterostomia. We aim to contribute towards redressing this balance with data on the development of the muscular, nervous and ciliary systems of the annelid Pomatoceros lamarckii (Serpulidae). We compare our data with other lophotrochozoans. RESULTS: P. lamarckii develops locomotory and feeding structures that enable it to become a swimming, planktotrophic larva within 24 hours. Formation of the trochophore includes development of a prototroch, metatroch and neurotroch, development of apical and posterior nervous elements at similar times, and development of musculature around the ciliary bands and digestive tract prior to development of any body wall muscles. The adult nervous and muscular systems are essentially preformed in the late larva. Interestingly, the muscular systems of the larvae and juvenile worms do not include the circular muscles of the body wall, which are considered to be plesiomorphic for annelids, although the possibility that circular muscles develop after these stages cannot be ruled out at this point. CONCLUSION: A comparison between polychaetes shows variability in the timing (heterochrony) of development of body wall muscles and elements of the nervous system. These heterochronies are one route for evolution of different life history strategies, such as adaptations to feeding requirements.